The impact of the COVID-19 preventive measures on influenza transmission: molecular and epidemiological evidence. (March 2022) - Tran, Leon King; Huang, Dai-Wei; Li, Nien-Kung; Li, Lucy M.; Palacios, Julia A.; Chang, Hsiao-Han
Abstract: Objective: We quantify the impact of COVID-19-related control measures on the spread of human influenza virus H1N1 and H3N2. Methods: We analyzed case numbers to estimate the end of the 2019−2020 influenza season and compared it with the median of the previous 9 seasons. In addition, we used influenza molecular data to compare within-region and between-region genetic diversity and effective population size from 2019 to 2020. Finally, we analyzed personal behavior and policy stringency data for each region. Results: The 2019−2020 influenza season ended earlier than the median of the previous 9 seasons in all regions. For H1N1 and H3N2, there was an increase in between-region genetic diversity in most pairs of regions between 2019 and 2020. There was a decrease in within-region genetic diversity for 12 of 14 regions for H1N1 and 9 of 12 regions for H3N2. There was a decrease in effective population size for 10 of 13 regions for H1N1 and 3 of 7 regions for H3N2. Conclusions: We found consistent evidence of a decrease in influenza incidence after the introduction of preventive measures due to COVID-19 emergence.